A Carbohydrate-Based Julia–Kocienski Reagent for Syntheses of Chain-Extended and C-Linked Saccharides - Bull, James A.; Kunz, Horst (Synthesis, 2014)
The carbohydrate-derived Julia–Kocienski reagent 2-{[(3aS,4S,6R,6aR)-6-methoxy-2,2-dimethyltetrahydrofuro[3,4-d][1,3]dioxol-4-yl]methylsulfonyl}-1,3-benzothiazole (6) was prepared from d-ribose and investigated in the eponymous olefination. The base-promoted generation of the Julia anion induced a rearrangement to the corresponding l-lyxose epimer 2-{[(3aS,4R,6R,6aR)-6-methoxy-2,2-dimethyltetrahydrofuro[3,4-d][1,3]dioxol-4-yl]methylsulfonyl}-1,3-benzothiazole (12), which reacted readily with aldehydes and with a gluconolactone. The latter reaction furnished an exo-glycal-linked C-diglycoside.
Keywords: chain-extended carbohydrates; Julia–Kocienski olefination; epimerization; lactone olefination; Smiles rearrangement